Low N Fertilizer Application and Intercropping Increases N Concentration in Pea (Pisum sativum L.) Grains - Hu, Falong; Tan, Yan; Yu, Aizhong; Zhao, Cai; Coulter, Jeffrey A.; Fan, Zhilong; Yin, Wen; Fan, Hong; Chai, Qiang (Frontiers in Plant Science, 2018)
Sustainable intensification of pulses needs reduced input of nitrogen (N) fertilizer with enhanced crop nutritional quality and yield. Therefore, increasing N harvest in grains (sink organs) by improving N remobilization is of key importance. Previous research has shown that a lower dose of N fertilizer effectively increases the rate of N remobilization, while intercropping improves the grain N concentration in pea (Pisum sativum L.). However, it is unknown whether intercropping can facilitate this N fertilizer effect to increase N remobilization, and thereby enhance the N harvest index (NHI). In this study, we determined N allocation among different organs of pea plants, N translocation from leaf and stem tissues to pods, N2 fixation, N utilization efficiency, and NHI of pea plants grown alone or intercropped with maize (Zea mays L.) with different N fertilization treatments in a field experiment in northwestern China from 2012 to 2014. A base application of 90 kg N ha−1 at sowing and top-dress application of 45 kg N ha−1 at flowering integrated with maize–pea intercropping increased N allocation to pod tissues, N translocation to grains, and NHI of pea plants. Compared with the application of 90 kg N ha−1 at sowing and 135 kg N ha−1 top-dressed at flowering, reducing the top-dress application of N fertilizer to 45 kg N ha−1 increased N allocation to intercropped pea plants by 8%. Similarly, N translocation to grains from leaf and stem tissues was increased by 37.9 and 43.2%, respectively, enhancing the NHI by 40.1%. A positive correlation between N2 fixation and NHI was observed, implying that N2 fixation improves N concentration in grain sinks. Thus, our data show that growing pulses in an intercropping system with reduced N fertilization are essential for maximizing N translocation, improving nutritional quality, and preventing the loss of N through leaching, thereby avoiding potential groundwater contamination.